Helical carbon nanofibers-supported MnSiO3 for high-performance lithium-ion battery anode materials - Jiang, Dongwei; Jin, Yongzhong; Zhang, Wenjun; Li, Xu; Chen, Ge; Liu, Yonghong (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2025)
[Display omitted] Metal silicates are regarded as promising candidates for lithium-ion batteries due to their high capacity, ease of synthesis, and environmental friendliness. Unfortunately, the challenge of enhancing the electrical conductivity of metal silicates represents a significant obstacle in this field. In this study, a simple and controllable two-step method was used to design and prepare the novel helical carbon nanofibers@manganese silicate (HCNFs@MnSiO3) anode composite, in which the size of MnSiO3 nanoparticles are about 20 nm. After 200 cycles at 200 mA g−1, the HCNFs@MnSiO3 anode exhibits an excellent reversible specific capacity of 878.1 mA h/g, which is 158 % higher than that of the MnSiO3 anode. The synergistic interaction of HCNFs and MnSiO3 is primarily responsible for the enhanced electrochemical performance of HCNFs@MnSiO3. A robust supportive network space is offered by the three-dimensional helical structure of HCNFs to allow for the volume expansion of MnSiO3 during charging and discharging. Furthermore, MnSiO3′s low electrical conductivity is enhanced by HCNFs’ high electrical conductivity. The development of high-performance lithium-ion batteries using metal silicate-based anode materials is aided by the useful reference provided by this study.